Integration versus segregation: Structural dynamics of a smallholder-dominated mosaic landscape under tree-crop expansion in Ghana. (May 2020) - Asubonteng, Kwabena O.; Pfeffer, Karin; Ros-Tonen, Mirjam A.F.; Baud, Isa; Benefoh, Daniel T.
Abstract: Tree crops like cocoa and oil palm have ecological and socio-economic significance in tropical landscapes. However, their expansion in tropical landscapes leaves footprints on ecosystem-based livelihoods, forests, and land for food. While policy and research have focused on productivity, markets and land-use transitions, the structural effects of expanding tree crops on landscapes have rarely been assessed. This study investigates changes in landscape structural properties associated with tree-crop expansion in a smallholder-dominated mosaic landscape. It quantifies the degree of integration/segregation in the landscape, and the direction in which the landscape evolves on an integration-segregation continuum. Landscape metrics from 1986 to 2015 land-cover maps were used to quantify landscape composition and configuration. Selected metrics were combined into a new composite landscape structural state index (LSSI), as a measure to determine the degree of integration/segregation. The study found that landscape composition was relatively stable. However, reduced patch numbers and complexity, and increased connectivity and aggregation revealed configurational dynamics: cocoa and oil palm exhibited aggregation tendencies; while food-crop areas became fragmented; and the LSSI indicated a shift towards greater segregation in the landscape between 1986 and 2015. Regarding structure, the smallholder landscape mimics an industrial agrarian landscape with large segregated homogenous cocoa and oil palm areas, and a reserved forest area. The study thus reveals changes in structural properties due to tree-crop led landscape transitions. It suggests considering these aspects when promoting tree crops in mosaic landscapes as they imply adverse effects on food availability and ecosystem services. Highlights: Tree-crop expansion changes landscape composition and configuration. Landscape metrics reveal a smallholder landscape that mimics large plantations. New Landscape Structural State Index (LSSI) assesses integration-segregation. Cocoa and oil palm areas have increased; food crop areas decreased. Implications for ecosystem services call for concerted landscape-level actions.